Market Orientation, Digital Branding, and Start-Up Growth: A Mediation Analysis of Brand Trust with a PLS-SEM Approach - Anggela Aine Adam; Githa Ils Rumambi; Priska Shirty Thelma Mawuntu (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
In an increasingly competitive digital environment, start-ups face substantial challenges in achieving sustainable growth while establishing strong market positions. Drawing on market orientation theory, digital branding, and relationship marketing, this study investigates the direct and indirect effects of market orientation and digital branding on start-up growth, with brand trust acting as a mediating variable. A quantitative research design was employed using survey data collected from 100 start-up owners and marketing managers operating in North Sulawesi, Indonesia. The proposed research model was tested using Partial Least Squares Structural Equation Modelling (PLS-SEM), which is appropriate for predictive models involving latent constructs and mediation effects. The findings reveal that both market orientation and digital branding exert significant positive effects on start-up growth. Digital branding demonstrates the strongest influence on brand trust, highlighting the critical role of consistent and interactive digital brand engagement in fostering consumer confidence. Brand trust, in turn, significantly enhances start-up growth and partially mediates the relationships between market orientation and growth, as well as between digital branding and growth. The results confirm that while strategic orientations directly contribute to growth outcomes, their impact is substantially strengthened through the psychological mechanism of brand trust. This study contributes to the digital marketing and entrepreneurship literature by providing empirical evidence on the mediating role of brand trust within an integrated PLS-SEM framework. From a managerial perspective, the findings emphasize the importance for start-ups to align market-driven strategies with coherent digital branding efforts to build trust and accelerate growth in digitally competitive markets.